Moderasi Dakwah Prophetic dalam Perspektif al-Qur’ân - Yusuf Baihaqi (Direktorat Jenderal Bimbingan Masyarakat Islam, 2018)
Moderation is an innate character that cannot be separated from Islamic teachings. Because of these moderation values, Islam is expected to be the best people among other people. Moderation of Islam covers all aspects of human life. In the world of da'wah, history records that the massive spread of Islam, both in the Arabian Peninsula and outside the Arabian Peninsula, was not due to coercion or warfare, but because of moderate da'wah, especially as exemplified by the Prophet Muhammad in his preaching and followed by his followers from the Moslem scholars of Ahl al-Sunnah Wa al-Jamâah. The formulation of moderate prophetic da'wah is realized, among others, by being a blessing to the community he advocates, promoting Akhlâq Karîmah and respecting diversity in preaching. Moderasi merupakan karakterik bawaan yang tidak bisa dilepaskan dari ajaran Islam. Karena nilai-nilai moderasi inilah, Islam diharapkan menjadi umat terbaik diantara umat-umat yang lain. Moderasi Islam mencakup segenap aspek kehidupan manusia. Dalam dunia dakwah, sejarah mencatat bahwasannya masifnya penyebaran Islam, baik di jazirah Arab maupun di luar jazirah Arab, bukanlah disebabkan karena faktor pemaksaan atau peperangan, melainkan karena dakwah moderat, khususnya yang dicontohkan oleh nabi Muhammad saw dalam dakwah beliau, dan diikuti oleh para pengikutnya dari kalangan ulama Ahl al-Sunnah Wa al-Jamâ`ah. Formulasi dakwah prophetic yang moderat terwujud diantaranya dengan menjadi rahmat bagi komunitas yang didakwahinya, mengedepankan Akhlâq Karîmah dan menghargai keberagaman dalam berdakwah